2018
DOI: 10.1177/2054358118793397
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Systemic Lupus Erythematosus With Lupus Nephritis in a 74-Year-Old Male: A Brief Case and Review

Abstract: Rationale:Late-onset systemic lupus erythematosus (SLE) represents a specific subgroup of SLE, and although there is no strict age cut-off, 50 years is commonly used as the minimum age for disease onset. In this report, we present a case of a 74-year-old male with late-onset SLE and biopsy-proven lupus nephritis (LN).Presenting concerns of the patient:A 74-year-old male was referred to the nephrology clinic with a rapidly rising creatinine from a baseline of 60 µmol/L to 176 µmol/L. His labs showed pancytopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, there are varying opinions on the prognosis and mortality as one study showed more favorable result [26] compared to the other [27]. Of note is that the oldest reported age of a patient diagnosed with late-onset SLE and lupus nephritis is 74 years [28]. Our patient was diagnosed with late-onset SLE at 77 years and developed stage IV LN at 79 years.…”
Section: Discussionmentioning
confidence: 81%
“…However, there are varying opinions on the prognosis and mortality as one study showed more favorable result [26] compared to the other [27]. Of note is that the oldest reported age of a patient diagnosed with late-onset SLE and lupus nephritis is 74 years [28]. Our patient was diagnosed with late-onset SLE at 77 years and developed stage IV LN at 79 years.…”
Section: Discussionmentioning
confidence: 81%
“…Serositis, interstitial pneumonia, and Sjogren's syndrome are frequently linked to late-onset SLE, while cutaneous manifestation, photosensitivity, arthritis, and nephritis occur less frequently. Elderly patients are frequently admitted to the hospital with nonspecifi c symptoms such as fatigue, weight loss, and acute kidney injury [7]. In the present case, in addition to exudative pleurisy and pericarditis, the patient had one of such musculoskeletal manifestations of SLE − unexpressed arthralgia of the small joints of the hand.…”
mentioning
confidence: 68%
“…The main differential diagnoses considered in our patient were whether the described associated glomerular disease is the paraneoplastic syndrome of lymphoma or that of concurrent primary lupus nephritis. However, new-onset SLE is uncommon in elderly male patients ( 8 ), and this patient notably has infiltration of mantle cell lymphoma cells in the renal interstitium and bone marrow. Besides, our patient achieved rapid remission of the glomerular disease and immune system remission after the first chemotherapy for MCL.…”
Section: Discussionmentioning
confidence: 99%